No evidence for genetic sex determination in Daphniamagna. Issue 6 (16th June 2021) - Cornetti, Luca; Ebert, Dieter
Abstract : Mechanisms of sex determination (SD) differ widely across the tree of life. In genotypic sex determination (GSD), genetic elements determine whether individuals are male or female, while in environmental sex determination (ESD), external cues control the sex of the offspring. In cyclical parthenogens, females produce mostly asexual daughters, but environmental stimuli such as crowding, temperature or photoperiod may cause them to produce sons. In aphids, sons are induced by ESD, even though GSD is present, with females carrying two X chromosomes and males only one (X0 SD system). By contrast, although ESD exists in Daphnia, the two sexes were suggested to be genetically identical, based on a 1972 study on Daphnia magna (2n=20) that used three allozyme markers. This study cannot, however, rule out an X0 system, as all three markers may be located on autosomes. Motivated by the life cycle similarities of Daphnia and aphids, and the absence of karyotype information for Daphnia males, we tested for GSD (homomorphic sex chromosomes and X0) systems in D. magna using a whole-genome approach by comparing males and females of three genotypes. Our results confirm the absence of haploid chromosomes or haploid genomic regions in D. magna males as well as the absence of sex-linked genomic regions and sex-specific single-nucleotide polymorphisms. Within the limitations of the three studied populations here and the methods used, we suggest that our results make the possibility of genetic differences among sexes in the widely used Daphnia model system very unlikely.